Effects of mild-to-moderate sensorineural hearing loss and signal amplification on vocal emotion recognition in middle-aged–older individuals - Ekberg, Mattias; Andin, Josefine; Signoret, Carine; Stenfelt, Stefan; Dahlström, Örjan (PLOS ONE, 2025)
Previous research has shown deficits in vocal emotion recognition in sub-populations of individuals with hearing loss. As emotion recognition is an essential ability that affects social interaction, and in extension, can impact well-being, understanding vocal emotion recognition difficulties is a high priority research topic. Furthermore, it has been shown that although hearing aids improves word recognition, it does not improve emotion recognition. To explore emotion recognition and the effect of amplification in individuals with hearing loss, we examined recognition of vocal emotions expressed both verbally and non-verbally in middle-aged to older individuals with and without linear amplification (similar amplification across sound levels). Twenty-one experienced hearing aid users with bilateral mild-to-moderate hearing loss, and 20 individuals with normal hearing performed a vocal emotion recognition task on sentences and non-verbal vocalizations. The hearing loss group had poorer emotion recognition for both sentences (F(1,38)=15.24, p <0.001, η2p=0.29, without linear amplification, and F(1, 38)= 5.62, p=0.023, η2p=0.13, with linear amplification) and non-verbal vocalizations(F(1,38)= 25.18, p <0.001, η2p=0.40, without linear amplification, and F(1, 38)= 10.30, p=0.003, η2p=0.21, with linear amplification). However, linear amplification significantly improved the recognition of happiness (p < 0.001), which is distinguished by frequency parameters, for sentences. For non-verbal vocalizations, recognition of fear (p = 0.004) and anger (p = 0.004), were improved by linear amplification. Patterns of confusion were similar for the two groups, which may suggest that both groups perceived the emotions similarly, but that the degree of perceptual precision was lower in the hearing loss group. In sum, hearing loss negatively impacts vocal emotion recognition, but linear amplification can enhance recognition for some emotions.